Advanced energy flow control concept of an MMC for unrestricted operation as a multiport device - Schröder, Markus; Jäger, Johann (IEEE Transactions on Power Electronics, 2019)
An advanced approach of the internal energy flow control of a multiport device based on a modular multilevel converter (MMC) was proposed. Such a multiport device offers various connecting points as ac terminals, the main dc terminal as well as the dc terminals of the MMC modules. State-of-the-art multiport concepts have restrictions concerning the flexibility of connecting the available ports. The proposed concept makes an unrestricted energy interchange between all ports possible without affecting the ac grid and the main dc terminal. It contains a microscopic and macroscopic view of the entire system and an analytic description in a double synchronous reference frame. This approach allows the identification of degrees of freedom for the internal energy flow control to overcome the mentioned restrictions of state-of-the-art multiport devices. Beyond numerous simulations calculations, the proposed concept has been implemented to a prototype of a multiport device which consists of an MMC with integrated batteries in power electronics laboratory. The approach has been successfully tested and verified with measurement results.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Batteries; converters; energy storage; multilevel systems

An Enhanced Modulator Concept for Modular Multilevel Converter - Schröder, Markus; Henninger, Stefan; Jäger, Johann (16th Conference on Power Electronics and Applications, 2014)
This paper deals with an enhanced modulator concept for the Modular Multilevel Converter. Based on an overview on existing concepts including module sorting algorithms and measurement results from a hardware-setup in laboratory, a new concept is developed. Measurement results of the implemented new algorithm for module selection and capacitor energy balancing in various operating points of the converter are presented and analyzed in detail. This elaboration is completed with a classification of the suggested modulator concept compared to established concepts.
Keywords: Modulation strategy; Multilevel converter; Pulse Width Modulation

Combining Frequency Containment Reserves and Renewable Power Leveling in Energy Storage Systems - Henninger, Stefan; Schröder, Markus; Jäger, Johann (Energy Procedia, 2016)

Energy balancing in the modular multilevel converter under unbalanced grid conditions - Schröder, Markus; Mahr, Florian; Jäger, Johann (19th European Conference on Power Electronics and Applications (EPE'17 ECCE Europe), 2017)

Grid-Forming Droop Control of a Modular Multilevel Converter in Laboratory - Henninger, Stefan; Schröder, Markus; Jäger, Johann (2018 IEEE POWER & ENERGY SOCIETY GENERAL MEETING (PESGM), 2018)
CRIS-Team WoS Importer:2019-02-22

Integration of Batteries into a Modular Multilevel Converter - Schröder, Markus; Henninger, Stefan; Jäger, Johann; Rasic, Andreja; Rubenbauer, Hubert; Leu, Holger (2013 15th European Conference on Power Electronics and Applications (EPE), 2013)
In this paper the challenges of integrating batteries into the Modular Multilevel Converter are described. For this purpose, the technology of this converter topology is briefly introduced. An overview on already available products of battery energy storage systems is given. Based on that, a control concept for a DC-to-DC converter connecting a battery to a module of the Modular Multilevel Converter is presented. This concept contains an additional energy balancing algorithm. Several operating points of the whole system with integrated batteries are simulated. The paper is topped off with measurement results of a started-up hardware setup that is equipped with emulated DC-to-DC converter

Measurement Results of a Modular Energy Storage System unevenly Equipped with Li-Ion-Batteries - Schröder, Markus; Henninger, Stefan; Jäger, Johann; Rubenbauer, Hubert (17th Europeans Conference on Power Electronics and Applications, 2015)
The objective of this paper was to present and evaluate measurement results of a battery energy storage system (BESS) that is based on a modular multilevel cascade converter (MMCC). The MMCC was unevenly equipped with lithium-ion batteries. The suggested concept of modular BESS was classified in the context of BESS based on modular converter topologies and was realized in a hardware-setup in laboratory. Therefore, different operation modes of the modular BESS were defined. Four different steady operation points of the entire system were investigated and evaluated. Finally, a concept of an active battery management system (BMS) was proved. It was shown that a modular BESS unevenly equipped with batteries offers several opportunities for BESS applications particularly with regard to the integration of different types of batteries into one single BES
Keywords: Batteries; Energy storage; Multilevel converters; Battery Managements Systems

Model-Based Predictive Control of a Modular Multilevel Converter - Mahr, Florian; Schröder, Markus; Jäger, Johann (Center of Knowledge Interchange (CKI), 2016)

The Idea of a Modular Multilevel Converter with Integrated Batteries - Schröder, Markus; Jäger, Johann (International Conference on Smart Grid Technology, 2012)
In this paper electro-chemical energy storing is discussed. Based on problems of currently available storage systems, the idea of using multilevel converters with distributed energy storages is introduced. Here, the Modular Multilevel Converter is focused after a general comparison with other multilevel converter concepts. To get familiar with this converter concept its characteristics and especially regulation aspects are illustrated. Necessary adaptions as well as investigations that have to be done to set up a Modular Multilevel Converter with integrated batteries are discusse